Founders, Jijamata Udyan - Ghosh, Ayan (2023)
Notable citizens of Mumbai who played a leading role in the establishment of Jijamata Bhonsle Udyan include Jagannath Shankarshet, David Sassoon, Dr. Bhau Daji Lad, George Birdwood, and Sir Jamsetji Jeejeebhoy. The garden was named after Queen Victoria to mark the transfer of power from the East India Company directly to the British Crown (in 1858).